2019
DOI: 10.1002/jaba.559
|View full text |Cite
|
Sign up to set email alerts
|

Learning a foreign language: Effects of tact and listener instruction on the emergence of bidirectional intraverbals

Abstract: We evaluated the effects of tact and listener instruction on the emergence of bidirectional intraverbal relations with 6 typically developing Brazilian children, using an adapted alternating treatment design with pretest and posttest probes. In listener instruction, participants selected pictures that corresponded to spoken foreign-language words. For tact instruction, children had to vocalize foreign words in the presence of the corresponding pictures. After meeting mastery criteria, bidirectional intraverbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 18 publications
3
30
1
1
Order By: Relevance
“…However, the differences between the present study and the studies conducted by Petursdottir and Hafliđadóttir (2009) and Petursdottir et al (2008) could be attributed to the differences in ages between participants. Nevertheless, more recent research has supported the findings of the present study in that foreign tact training was effective in producing emergent responding bidirectionally in the intraverbal relations (e.g., Cortez et al, 2020). Given that there are only three studies that previously researched response maintenance following behavior analytical training in foreign language instruction using different methodologies, it is difficult to make comparisons with the present findings.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…However, the differences between the present study and the studies conducted by Petursdottir and Hafliđadóttir (2009) and Petursdottir et al (2008) could be attributed to the differences in ages between participants. Nevertheless, more recent research has supported the findings of the present study in that foreign tact training was effective in producing emergent responding bidirectionally in the intraverbal relations (e.g., Cortez et al, 2020). Given that there are only three studies that previously researched response maintenance following behavior analytical training in foreign language instruction using different methodologies, it is difficult to make comparisons with the present findings.…”
Section: Discussionsupporting
confidence: 43%
“…A more recent study by Cortez, dos Santos, Elisa Quintal, Silveira, and de Rose (2020) also shows the variability in the efficiency of behavioral training methods in children, providing further evidence for the independence of verbal relations. Cortez et al (2020) examined the effect of foreign tact and listener responses on the emergence of bidirectional intraverbal relations. Researchers in this study found that foreign tact training was effective in producing emergent responding bidirectionally whereas following training in foreign listener relations emergent responding in the bidirectional intraverbal relations was variable across participants, with neither emergent intraverbal relation reaching criterion even though greater levels of emergent responding were found in the N-F intraverbal relation.…”
mentioning
confidence: 99%
“…Overall, these studies focused on teaching a subset of skills (e.g., listener and tact responses) and probing the emergence of others (e.g., intraverbal responses) to evaluate the most effective and efficient arrangements. The current study represents a systematic replication of Petursdottir et al (2008) and Cortez et al (2020), both of which compared the effects of tact and listener instruction on the emergence of bidirectional intraverbals (i.e., native to foreign and foreign to native).…”
mentioning
confidence: 55%
“…There is a growing body of literature examining the effectiveness of teaching a foreign language using behavior‐analytic procedures (Cortez et al, 2020; Daly & Douvani, 2020; Davidson & O'Connor, 2019; Dounavi, 2011, 2014; Matter et al, 2020; May et al, 2016, 2019; Petursdottir & HafliĐadóttir, 2009; Petursdottir et al, 2008; Rosales et al, 2012; H. Wu & Miller, 2007; W. L. Wu et al, 2019). Overall, these studies focused on teaching a subset of skills (e.g., listener and tact responses) and probing the emergence of others (e.g., intraverbal responses) to evaluate the most effective and efficient arrangements.…”
mentioning
confidence: 99%
“…(2) a escassez de estudos sobre o efeito do SPOP na aquisição deste operante verbal; (3) a dificuldade de aquisição de intraverbais por crianças com TEA e sua importância para o desenvolvimento de habilidades sociais e acadêmicas (Sundberg & Sundberg, 2011); e (4) a importância de estabelecer repertórios socialmente relevantes como o aprendizado de segundo idioma (Cortez, Santos, Quintal, Silveira, & de Rose, 2019;Pérez-González, Herszlikowicz, & Williams, 2008), o presente estudo procurou comparar a eficácia do SPOP com um procedimento de apresentação contígua de estímulos (PACE) com requisição de resposta ecoica, 2015; Carnerero, Pérez-González, & Osuna, 2019;Vallinger-Brown & Rosales, 2014).…”
unclassified